2020
DOI: 10.1002/lno.11578
|View full text |Cite
|
Sign up to set email alerts
|

Hypolimnetic oxygen depletion rates in deep lakes: Effects of trophic state and organic matter accumulation

Abstract: This study investigated the consumption of oxygen (O 2) in 11 European lakes ranging from 48 m to 372 m deep. In lakes less than~100 m deep, the main pathways for O 2 consumption were organic matter (OM) mineralization at the sediment surface and oxidation of reduced compounds diffusing up from the sediment. In deeper lakes, mineralization of OM transported through the water column to the sediment represented a greater proportion of O 2 consumption. This process predominated in the most productive lakes but de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 61 publications
4
32
2
Order By: Relevance
“…Due to bottom water aeration, the O 2 concentration remained high in this lake. The rapid depletion of O 2 , NO 3 - , NO 2 - and SO 4 2- and the increasing concentration of NH 4 + with sediment depth indicated a high level of respiration activity, which is in line with previous reports 20, 42, 62 . Lake Sarnen, in contrast, showed similar sediment porewater profiles as other oligotrophic lakes, e.g., Lakes Lucerne 42 , Brienz, or Thun 62 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to bottom water aeration, the O 2 concentration remained high in this lake. The rapid depletion of O 2 , NO 3 - , NO 2 - and SO 4 2- and the increasing concentration of NH 4 + with sediment depth indicated a high level of respiration activity, which is in line with previous reports 20, 42, 62 . Lake Sarnen, in contrast, showed similar sediment porewater profiles as other oligotrophic lakes, e.g., Lakes Lucerne 42 , Brienz, or Thun 62 .…”
Section: Discussionsupporting
confidence: 92%
“…The rapid depletion of O 2 , NO 3 - , NO 2 - and SO 4 2- and the increasing concentration of NH 4 + with sediment depth indicated a high level of respiration activity, which is in line with previous reports 20, 42, 62 . Lake Sarnen, in contrast, showed similar sediment porewater profiles as other oligotrophic lakes, e.g., Lakes Lucerne 42 , Brienz, or Thun 62 . However, compared to these lakes, the N compound concentrations in Lake Sarnen were lower, the O 2 and SO 4 2 concentrations, and O 2 penetration depth higher, which could be a sign of lower respiratory activity (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The structural equation model shows a significant positive effect 503 between HRT and autochthonous POC, which can be explained by an increase in 504 phytoplankton photosynthesis (Crawford et al, 2016). Previous investigations have shown that autochthonous POC in lake reservoirs with depths greater than 100 m was completely mineralized before carbon burial (Steinsberger et al, 2020). Autochthonous POC can be rapidly used to produce CH4, while the decomposition of terrestrial POC was slower (Grasset et al, 2018;Isidorova et al, 2019 S10).…”
Section: Cascade Damming Effect On Input and Accumulation Of Pocmentioning
confidence: 92%
“…The input of organic material is often not be considered in relation to the observation of lake waters condition. Meanwhile, as is known, organic material could have an impact on oxygen availability [25], especially in the hypolimnion zone, and the catchment area also contributes to the hypolimnion condition [26]. Thus, organic materials, which are indicators of domestic pollution, are important to be considered.…”
Section: B Impact Of Pollutant Loadsmentioning
confidence: 99%